O pensamento de Celso Furtado e a construção de um projeto nacional - DOI: 10.5752/P.2237-8871.2011v12n16p86 - Mourão, Rafael Pacheco; Veriano, Carlos Evangelista (Cadernos de História, 2011)
O presente artigo discute o pensamento de Celso Furtado tendo por tema central a defesa de que há em sua obra um projeto nacional para o Brasil. Pretende-se destacar que esse projeto nacional extrapola a diretiva do viés econômico e contempla também os aspectos políticos, sociais e culturais, ou seja, que propõe “desenvolvimento” no rigor da definição furtadiana, de modo que o mesmo desaguaria na construção de uma Nação republicana e democrática, economicamente forte e com equidade social. Abstract This article discusses the thought of Celso Furtado having as its central theme the defense that there is in his work a national project for Brazil. Noting that this national project goes beyond in the right of the economic bias and also includes the political, social and cultural aspects, on the other words, it proposes "development" in the stringency of the furtadian definition. Thus, this project flows into a building of a republican and democratic nation, economically strong and with social equity. Key words: Celso Furtado; National Project; Development; Democracy; Nation.